MOOCs in Malaysia towards globalised online learning - Farrah Dina Yusop; Rosemaliza Kamalludeen; Zahiruddin Fitri Abu Hassan; Mohd. Shukri Nordin (Penerbit UPNM, 2020)
Massive open online courses or MOOC made its debut in 2008 and revolutionised the higher education scene, providing wider access to courses and universities, and remodel university education.